If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(5x + -5) = x + 13 Reorder the terms: 3(-5 + 5x) = x + 13 (-5 * 3 + 5x * 3) = x + 13 (-15 + 15x) = x + 13 Reorder the terms: -15 + 15x = 13 + x Solving -15 + 15x = 13 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -15 + 15x + -1x = 13 + x + -1x Combine like terms: 15x + -1x = 14x -15 + 14x = 13 + x + -1x Combine like terms: x + -1x = 0 -15 + 14x = 13 + 0 -15 + 14x = 13 Add '15' to each side of the equation. -15 + 15 + 14x = 13 + 15 Combine like terms: -15 + 15 = 0 0 + 14x = 13 + 15 14x = 13 + 15 Combine like terms: 13 + 15 = 28 14x = 28 Divide each side by '14'. x = 2 Simplifying x = 2
| 87=-3(5k-9) | | 7.8=3+0.1n | | -3/1p=-33 | | 3x-33=18x-360 | | 3x+2+5x+10=180 | | 4(2r-5)=-100 | | Sin^2-2sinx-4=0 | | -29-31+x=-16 | | 6x=360-30 | | 3x-12=-4 | | 0.1y+x=18 | | 5/3a=35 | | gt+k-h=81t^2 | | x+3+x+80=180 | | 19+4h=-1-5h | | 5/15=2/6] | | 5/3a=36 | | 40x^2-59x+21=0 | | -81t^2+k-h=-gt | | -12+4j=4 | | 38x+9=21 | | 13=4+3v | | Y=-4.5x+40.333 | | x-5=2x+11 | | F(6)=8x+2 | | 17g+3=11g+9 | | 5/7m=4/5 | | 6+-3d=-6 | | 8/n-12=-8 | | Fx=3x-10 | | 0.54=ln(y) | | 3c+22=12-27c |